Numerical simulation of the femur fracture with and without prosthesis under static loading using extended finite element method (X-FEM) / Zagane Mohammed El Sallah … [et al.] - Mohammed El Sallah, Zagane; Ismail, Benbarek; Ali, Benouis; Abderahmen, Sahli; Bel Abbes, Bachir Bouiadjra; Serier, Boualem (Faculty of Mechanical Engineering Universiti Teknologi MARA (UiTM), 2017)
The strength of the bone depends on its mineralization state and its geometry, which depend on the loads supported. Thus the bone optimizes its mass and its geometry through the process of remodeling and improves its lift. This phenomenon can be altered by metabolic imbalances such as fall or trauma. The result is fractures, the most important of which are the proximal femur. The direct consequence of this type of fracture is the replacement of the joint by a Total Hip Prosthesis (PTH). The number of prosthetic implantations continues to increase given the longer life expectancy of patients.. This study is to compare the modeling to identify regions of fracture risk of femur and after the location of the total hip prosthesis (THP) by the extended finite element method (X-FEM) under static stress for a deferent orientation loading and for two materials (isotropic / orthotropic). The results show that the distribution of von mises stresses in the components of the femoral arthroplasty depends on the material and the design of the stem and show that the vertical loading leads to fracture of the femoral neck and the horizontal loading leads to the fracture of diaphysis femoral. The isotropic consideration of bone leads to bone fracture by propagation of the fissure, but the orthotropic consideration leads to the fragmentation of the bone. This modeling will help to improve the design of the indoor environment to be safer for the means of passenger transport.